Weather and daily mobility in international perspective: A cross-comparison of Dutch, Norwegian and Swedish city regions - Böcker, Lars; Priya Uteng, Tanu; Liu, Chengxi; Dijst, Martin (Transportation research. Part D, Transport and environment, 2019)
•We analyse weather effects on trip purpose, trip chaining, distance and mode choice.•We use national travel survey data, weather records and structural equation modelling.•Light, warm, calm and dry conditions may increase cycling and outdoor leisure.•Dark, cold, wet and windy conditions may enhance car use and trip chaining.•We find clear differences between Dutch, Norwegian and Swedish city regions. With climate change, weather has emerged as an important theme in transport research and planning. Although recent studies demonstrate profound weather effects on mobility in single case study areas, international cross-comparisons are required to reveal how effects differ between cities with different transport and climate regimes. This paper provides an international cross-comparison of the simultaneous effects of weather on destination choices, distances, trip chaining, and transport modes in the urban regions of Utrecht (Netherlands), Oslo and Stavanger (Norway), and Stockholm (Sweden). Hereto, regional subsamples of national travel survey data were linked to meteorological records for the three respective countries and analysed in generalised Structural Equation Models. Our findings generally indicate that light, calm, dry and warm atmospheric conditions may positively affect cycling and the selection of outdoor leisure destinations, while cold and to a lesser extent wet and windy weather conditions reduce cycling and enhance car use and travel optimising strategies like trip chaining, to reduce weather exposures. A positive effect of air temperature on cycling flattens out above 20–25 °C in most of our study areas, but hot weather does not seem to reduce cycling strongly. However, our findings also show considerable regional differences in the effects of weather on mobility. Both general effects and differences are interpreted in relation to geographical context, transport and land use, climate conditions, cultures, habits and adaptations and are discussed to formulate policies to mitigate active transport mode users’ exposures to adverse weather and make walking and cycling (even more) year-round modes.